Multiplex gene editing enables the multibiofortification of essential vitamins and other health-promoting phytonutrients in tomato - Yechun Hong; Zongjun Yu; Wenbo Zhu; Jialei Sun; Zeyao Zhu; Zhen Wang; Minjie Cao; Zhaobo Lang; Yu-Xuan Lyu; Pengpeng Liu; Jian-Kang Zhu (Proceedings of the National Academy of Sciences, 2026)
Dietary deficiencies in essential micronutrients and other phytonutrients represent a global health and economic burden, contributing to “hidden hunger” and chronic diseases. While genome editing has been employed to improve individual nutritional traits in crops, multibiofortification through simultaneous modification of multiple distinct metabolic pathways is more challenging. Here, we designed a multiplex CRISPR-Cas strategy to edit five key genes in tomato: Sl7-DR2 , SlGAD3 , SlSGR1 , SlGGP1 , and SlGGP2 . This approach successfully generated quintuple mutant ( 5m ) tomato lines simultaneously biofortified with seven health-promoting compounds: vitamin D 3 (from 0 to 0.70 μg/g dry weight), vitamin C (up to 2.53-fold), provitamin A/β-carotene (up to 3.86-fold), α-carotene (up to 2.47-fold), lutein (up to 3.26-fold), lycopene (up to 7.07-fold), and γ-aminobutyric acid (GABA, up to 5.26-fold). Notably, these multibiofortified tomatoes exhibited no significant trade-offs in plant growth or fruit quality. Extracts from 5m tomatoes showed enhanced suppression of colorectal cancer cell proliferation in vitro. This antiproliferative effect was validated in vivo, where dietary supplementation with 5m tomato powder significantly inhibited tumor growth in a mouse xenograft model. Our work demonstrates an effective strategy for developing a next generation of “functional foods” through multibiofortification, creating a single, nutrient-dense crop that combats both micronutrient malnutrition and chronic diseases.